Determining the Maximum States of the Ensemble Distribution of Boolean Networks - Cui, Xiaodong; Ren, Binghao; Li, Zhenghan (Frontiers in Physics, 2021)
Inference of the gene regulation mechanism from gene expression patterns becomes increasingly popular, in recent years with the advent of microarray technology. Obtaining the states of genes and their regulatory relationships would greatly enable the scientists to investigate and understand the diseases mechanisms. However, it is still a big challenge to determine relationships from several thousands of genes still remains as a chanllege. Here, we simplify the above complex gene states determination problem as an inference of the distribution of the ensemble Boolean Networks (BNs). In order to investigate and calculate the distribution of the BNs’ states, we ﬁrst compute the probabilities of the diﬀerent BNs’ states and obtain the number of states Ω. Then, we ﬁnd the maximum possible distribution of the number of the BNs’ staes and calculate the ﬂuctuation of the distribution. Finally, two reprentative experiments are conducted and the eﬃciency of the obtained results are veriﬁed. The proposed algorithm is conceptually concise and easily applicable to many other realistic models; furthermore, it is highly extensible for various situations.